Simple weighing lysimeters for measuring evapotranspiration and developing crop coefficients - Fisher, Daniel K. (International Journal of Agricultural and Biological Engineering, 2012)
Knowledge of cotton crop evapotranspiration (ET) is important in scheduling irrigations, optimizing crop production, and modeling ET and crop growth. The ability to measure, estimate, and predict ET and cotton crop water requirements can result in better satisfying the crop